2020
DOI: 10.1111/jace.16972
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of molten silicate deposits with yttrium monosilicate

Abstract: The article addresses effects of silicate deposit composition on reactions with yttrium monosilicate (YMS), a candidate environmental barrier coating for aero-engine components. Computed phase equilibria are used to predict the nature and relative proportions of reaction products and the extent of YMS consumption upon reaction with twelve deposits of varying composition at 1300°C. These predictions are compared with results of a corresponding experimental study on three exemplary deposits.Although the nature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 33 publications
3
37
0
1
Order By: Relevance
“…30 With respect to recession, it can be assumed that the dense fringe acts as a protective layer against CMAS infiltration or Ca 2+ diffusion. This assumption is supported by the results of Summers et al 37 They observed a dense fringe at the interface of the reaction zone and remaining YbMS as well as reduced recession of the MS, which was only 50% of the amount they predicted.…”
Section: Ybds µMsupporting
confidence: 69%
See 3 more Smart Citations
“…30 With respect to recession, it can be assumed that the dense fringe acts as a protective layer against CMAS infiltration or Ca 2+ diffusion. This assumption is supported by the results of Summers et al 37 They observed a dense fringe at the interface of the reaction zone and remaining YbMS as well as reduced recession of the MS, which was only 50% of the amount they predicted.…”
Section: Ybds µMsupporting
confidence: 69%
“…Both reported that with increasing Ca:Si ratio, the formation of apatite Ca 2 RE 8 (SiO 4 ) 6 O 2 phases as the primary reaction product is promoted. In addition, the recession became more pronounced as more RE silicate material was necessary to stop the CMAS attack 35,37 . Furthermore, Stokes reported that at high Ca:Si ratios above 0.72 only apatite is formed and that for lower ratios the silicates of smaller RE cations, such as Yb, have a tendency to form additional metastable reaction products 35 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, rare earth (RE)-doped silicates, which have very good oxidation resistance and can withstand high temperatures, are attracting attention for this kind of application. [22][23][24][25][26]…”
mentioning
confidence: 99%